Case Studies Of Progressive Pillar Failure In Two Mines Using Wide Pillars - Hamid Maleki (International Conference on Ground Control in Mining, 2000)
Results of geologic investigations, in-mine instrumentation, and numerical modeling are presented for two longwall mines in which pillars with large width-to-height ratios (8 to 9) are used. These investigations revealed that wide pillars unload when subjected to sufficient stress and that pillar unloading is influenced by geologic conditions. Field measurements in mine 1 clearly indicated load transfer from the longwall area toward the gate roads, resulting in pillar failure near the margin of a fluvial channel. Loads were shown to transfer to a harrier pillar (width height ratio equal to 9), contributing to progressive failure of this pillar. Unloading of the barrier pillar was associated with significant load transfer to the two-seam submains to the north of the harrier, contributing to roof falls, floor heave, and rib spalling within the submains. Stress analysis results addressed pillar peak strength and unloading behavior that was in agreement with the measurements and underground observations. Underground observations and stress analyses were completed before and after longwall mining near a six-entry submain in mine 2. This submain was intended to he used as a temporary bleeder and tailgate for a small longwall block consisting of one to two panels, depending on the development schedule in other areas of the trine and observed ground conditions. Numerical modeling using both elastic and inelastic pillar behavior for submain pillars with a width-to-height ratio of 8 was completed before mining began. Results indicated that pillar unloading was likely. During retreat of the first longwall panel, pillars unloaded. as evidenced by progressive rib spalling along the cleats, This behavior was mostly confined to the immediate face area, an observation that was in agreement with the modeling results,